Parental concerns definition: a literature review - Algarvio,Susana (2016)
Background: The evaluation of parental concerns is considered of extreme importance in clinical practice, confirmed by current research. However, criteria for the definition of parental concerns are not standardized, and reflect different levels of analysis. The purpose of this study was to build a descriptive literature base of the current research on parental concerns. Methods: An extensive search was conducted using MEDLINE, ERIC, PsycINFO, PsycARTICLES, Academic Search Complete, Education Research Complete, PEP Archive, and Psychology and Behavioral Sciences Collection databases. The key words used were parental concerns. Criteria for inclusion were: peer-reviewed publications, parental concerns’ assessment, issue of interest for general parenting. Results: A total of 4130 publications were abstracted and reviewed, 128 were selected for inclusion. Themes from these papers were identified and were grouped according to seven main outcome categories: Parental concerns’ definition, parental concerns’ determinants, parental concerns predictive of children’s problems, parental concerns predictive of parental behaviour, parental concerns’ outcomes, parental concerns’ influence on healthcare professionals, and parental concerns and intervention strategies. Conclusions: Evidence demonstrated that parental concerns are an expected and positive aspect of parenting. They influence parental behaviour and thus promote positive outcomes in children. Parental concerns presented high sensitivity regarding children’s problems, being considered as effective as formal testing. General parental concerns, the factors that influence them and the related outcomes should be considered in future studies. Further research should also address the development of standardized instruments for the assessment of general parental concerns.